تطوير مادة تعليم النحو بالمنهج الاستقرائي في الندوة الأسبوعية بشعبة تدريس اللغة العربية في الجامعة الإسلامية الحكومية فالوفو - Firmansyah, Odhika; M Zuhri Abu Nawas; Alfan Putra (Al Ibrah: Journal of Arabic Language Education, 2024)
This research examines the implementation of a selective method combined with comic storytelling techniques to enhance Arabic speaking skills among eleventh-grade students. The objectives are to: (1) analyze how the selective method with comic storytelling improves students’ speaking skills and (2) evaluate the outcomes of its application. Conducted as Classroom Action Research (CAR), the study involved two cycles, each consisting of planning, action, observation, and reflection. The results demonstrate a notable improvement in students' speaking abilities. The average score increased from 69.58 before the intervention to 75.15 in the first cycle and 92.92 in the second cycle, classified as "very excellent." Additionally, the percentage of students achieving the minimum competency standard rose from 15% pre-intervention to 61.5% after the first cycle and reached 100% in the second cycle. This method fosters an engaging learning environment by integrating visual and narrative elements, addressing diverse student learning styles, and minimizing classroom monotony. The approach effectively enhances students' active participation and speaking performance, making it a valuable alternative for Arabic language instruction. This study suggests that combining selective methods with comic storytelling is a creative and impactful strategy for developing Arabic speaking skills. يتناول هذا البحث تطبيق الطريقة الانتقائية باستخدام تقنية سرد القصص المصورة لتحسين مهارة الكلام باللغة العربية لدى طالبات الصف الحادي عشر. تهدف الدراسة إلى: (1) تحليل كيفية تحسين الطريقة الانتقائية مع تقنية سرد القصص المصورة لمهارة الكلام، و(2) تقييم نتائج تطبيقها. أُجريت الدراسة باستخدام منهج البحث الإجرائي الصفي (CAR)، الذي تضمن دورتين تشملان مراحل التخطيط، والتنفيذ، والملاحظة، والتقييم. أظهرت النتائج تحسناً ملحوظاً في مهارات الطالبات في الكلام. ارتفع متوسط الدرجات من 69.58 قبل التدخل إلى 75.15 في الدورة الأولى، ثم إلى 92.92 في الدورة الثانية، مما يُصنَّف ضمن الفئة "ممتاز جداً". كما ازدادت نسبة الطالبات اللواتي حققن الحد الأدنى من الكفاءة من 15% قبل التدخل إلى 61.5% بعد الدورة الأولى، ووصلت إلى 100% في الدورة الثانية. ساهم هذا النهج في خلق بيئة تعليمية محفزة ومشوقة، حيث جمع بين العناصر البصرية والسردية التي تلائم أنماط التعلم المختلفة للطالبات، مما قلل من الملل داخل الصف. يوصى باستخدام الطريقة الانتقائية وتقنية سرد القصص المصورة كاستراتيجية مبتكرة وفعالة لتعزيز مهارات الكلام في تعليم اللغة العربية.